The Influence of Energy Drinks on Lower Limb Muscle Fatigue and Recovery in Healthy Young Adults - Rosario, Martin G; Costet, Alexandre; Berlof, Logan (Journal of Sports Research, 2022)
Many studies have researched the influences of energy drinks (Edrinks) on the central nervous system, balance, and neuromuscular control. Understanding the neuromuscular adaptations that occur after drinking Celsius Edrinks on muscle fatigue and balance can be helpful when advising the use of Edrinks during physical activity. This study aims to understand the impact Celsius Edrinks has on neuromuscular adaptations in lower limb musculature during muscle fatigue, and balance in young, healthy adults. Two males and eighteen females were recruited for this study. The tibialis anterior, gastrocnemius, and Gluteus Medius neuromuscular data were captured with surface EMG electrodes. The number of single-leg heel raises repetitions and time to fatigue were recorded. Subjects were asked to perform single-leg heel raises to fatigue and single-leg balance activities pre-energy drink consumption, and the same tasks were repeated on the opposite not tested limb (post Edrinks consumption) to equate data points. Neuromuscular timing data suggested modifications on leg musculature. Although not significant, the amount of single-leg heel raises performed pre, and post-drink intake increased post-energy drink consumption. We infer that the ingredients in Celsius energy drinks, including caffeine, Taurine, and Guarana, alter nerve conduction velocity in lower limb musculature during exercise and balance activities. Future studies should research the influence of Celsius energy drinks in different scenarios and populations.